The Influence of Customer Experience and Store Atmosphere Towards Revisit Intention at Heira House Coffee & Studio - Siswat Siswat; Mardiana Nisa B; Tias Prawitasari (Universitas Veteran Bangun Nusantara, 2025)
This study analyzes the effect of Customer Experience (X1) and Store Atmosphere (X2) on Revisit Intention (Y) at Heira House Coffee & Studio. The method used is quantitative descriptive with 100 respondents selected through accidental sampling technique. Data collection was carried out using online and offline questionnaires, and analyzed using multiple linear regression. The results showed that Customer Experience and Store Atmosphere each had a positive and significant effect on Revisit Intention with a calculated t value of 3.141 and 3.001> t table value of 1.985 and a significance of 0.002 and 0.003 <0.05. Simultaneously, these two variables also have a significant effect on Revisit Intention with F count 17.002 > F table 3.090. The results of the determination coefficient test obtained an R Square value of 0.687. This means that 68.7% of the influence of the Customer Experience and Store Atmosphere variables on Revisit Intention. The more positive the visitor's experience and the more attractive the cafe atmosphere, the higher the likelihood of a repeat visit. Heira House Coffee & Studio is advised to continue to improve its services and products to maintain and increase the number of visitors.